RNEL and Lithium Werks Partnership - Reliance Industries Limited (2022)
RNEL continues to build the New Energy ecosystem by acquiring assets of LFP batteries provider Lithium Werks for USD 61 million. Lithium Werks is a leading provider of cobalt free and high-performance Lithium Iron Phosphate (“LFP”) batteries.